VALUES OF MORAL EDUCATION IN THE BOOK USWATUN HASANAH BY NUKMAN SULAIMAN - Maya Sari, Ita; OK, Azizah Hanum; Arsyad, Junaidi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to describe the relevance of moral education values ​​in the book uswatun hasanah with Islamic education in modern times. The type of research used in this study is qualitative research. The research design uses library research and the research approach is a study of figures. The data sources used are written sources by collecting works of figures and related previous studies. The results of this study indicate that the specifications of moral education values ​​according to Nukman Sulaiman are to form humans who have noble character, obey Allah and His Messenger, love both parents, honor teachers, respect family, love orphans, respect neighbors, be honest, trustworthy, patient, shy, brave, friendly, polite, have high ideals, 'iffatun, believe in yourself, be diligent, help each other, and be sincere. The values ​​of moral education from Nukman Sulaiman's perspective according to the researcher's goals are still relevant to today's education. This is proven by the fact that Nukman Sulaiman's educational goals are still applied in the Al Washliyah Education System, Articles 2, 3 and 4 concerning the vision, mission and goals of education.